Analisis Bibliometrik Trend Penelitian Pemodelan Matematis Menggunakan Database Google Scholar, Publish or Perish, dan Vosviewer - Komang Ariyanto (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to identify the topic of the study of mathematical modeling by highlighting publications on Google Scholar from 1951 to 2022. This study uses the Google Scholar citation database for 71 years to collect articles. The keyword used in this research is "mathematical modeling" with a filter of English documents. Simple statistical methods were used, and bibliometric analysis was performed using Publish or Perish and Vos-viewer software. This study visualizes the co-occurrence patterns of keywords and citations. This study reveals a significant research trend in the field of mathematical modeling from 71 years ago. Based on the visualization of the large cluster network map which includes mathematical modeling concepts, it is known that the health sector is dominant as the background for its presence. Study of the topic of mathematical modeling still revolves around theoretical developments, economics, industry and environment. However, there has been no study of mathematical modeling in the social and cultural fields. Moreover, by using the bibliometric method to re-identify keywords that are in accordance with the development of problem solving through mathematical models